PENINGKATAN KETERAMPILAN DAN PEMBERDAYAAN EKONOMI MELALUI PELATIHAN PEMBUATAN KOMPOS BAGI NASABAH BANK SAMPAH BTN PASSO INDAH AMBON - Tomasoa, Reny; Turukay, Martha; Lawalata, Imelda J.; Hehanussa, Meitty L.; Kailola, Joan J. G.; Matatula, Erfina A. (Universitas Pattimura, 2025)
The BTN Passo Indah Waste Bank in Negeri Passo, Ambon City, is a community-based initiative focused on sustainable waste management. This waste bank aims to reduce the volume of waste disposed of and to increase public awareness of the importance of recycling. However, one of the main challenges faced is how to process organic waste effectively and efficiently. A practical solution to this issue is to convert organic waste into compost fertilizer. The implementation of the solid organic fertilizer (compost) training for the members of the BTN Passo Indah Waste Bank was carried out through three main stages: planning, theoretical training, and practical training. During the planning stage, participants were identified, training materials were prepared, and tools and materials were organized. The theoretical stage focused on understanding the concepts of organic waste management, the basic principles of composting, and the factors influencing the composting process. As a result of this training, community knowledge increased by 90%, and practical skills improved by 85%. The compost produced can be utilized by farmers in Negeri Passo to naturally enhance agricultural yields without relying on chemical fertilizers, reduce production costs, and maintain long-term soil health. Furthermore, this training opens up new economic opportunities for waste bank members, as the organic fertilizer produced can be sold to generate additional income for the local community.